Foucault na educação: ferramentas analíticas para a práxis educacional hoje - Valeirão, Kelin (2009)
This thesis seeks to reflect on how the power governamentality relation can contribute to today s educational praxis, based on Foucault s thought categories. From the understanding that the questioning Was ist Aufklärung? guides the diagnosis of Foucault s philosophy in a present-day ontology, we go back in philosophy history and propose that, while Kant elaborates the present from the Aufklärung concept, Foucault lays the foundation of his critical genealogy on the neologism governamentality , which is power technology operating at its full, a research tool, a lens that allows us to see how safety devices work. Leading the discussion towards Education, we realize that the educational praxis is a new way to guide children s behavior nowadays. It is not, however, something entirely detached from the educational praxis that existed until then, typical of a disciplinary society. We should not understand such passages as compartmentalized substitutions from one society to another, once realizing the present we live in a clearer way demands the perception of the shift from a disciplinary society towards a control one, as well as the study of the way this movement is connected, not only to a specific manner of conducting people s behavior but also linked to the so-called education crisis . It seems that today s educational praxis acts as a device that works in harmony with a specific governamentality model. Thus, on thinking of the connection between governamentality and educational praxis today, we realize that the latter is to be found inside a discursive order which supports control society governamentality, and is in turn supported by the former.